Robust Watermarking using Genetic Algorithm in DCT Domain - Vikram Singh, Raj; Waria, Subodh; Kumar Singh, Rajiv; Vikram Singh, Harsh (International Journal of Engineering and Technology, 2018)
In this paper, a novel and efficient data hiding using Genetic Algorithm in DCT Domain implemented. Watermarking is an essential zone of research as of late including various applications. It is the investigation of inserting data into the cover picture viz., content, video, and picture (payload) without making measurably huge change the cover picture.Â Â